2016
DOI: 10.5267/j.ijiec.2015.8.002
|View full text |Cite
|
Sign up to set email alerts
|

Competitive location: a state-of-art review

Abstract: This paper provides a review on recent works in the field of competitive facility location models based on the following seven components: 1) Variables, 2) Competition type, 3) Solution space, 4) Customer behavior, 5) Demand type, 6) Number of new facilities and 7) Relocation and redesign possibility. First, the components are introduced and then based on these components; different studies are compared with each other via a proposed taxonomy and finally a review on work of each paper is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 66 publications
0
11
0
3
Order By: Relevance
“…They rather assume that facility attractiveness levels are randomly distributed in the sense that customers have varying perception for the design of facilities and develop two solution procedures for locating p number of facilities. A detailed overview of CFL models can also be found in [24]. This study categorizes the CFL problems using seven components, namely decision variables, competition type, solution space, customer behavior, demand type, number of new facilities to locate, and the possibility for relocation and redesigning of existing facilities.…”
Section: The Book By Farahani and Hekmatfarmentioning
confidence: 99%
“…They rather assume that facility attractiveness levels are randomly distributed in the sense that customers have varying perception for the design of facilities and develop two solution procedures for locating p number of facilities. A detailed overview of CFL models can also be found in [24]. This study categorizes the CFL problems using seven components, namely decision variables, competition type, solution space, customer behavior, demand type, number of new facilities to locate, and the possibility for relocation and redesigning of existing facilities.…”
Section: The Book By Farahani and Hekmatfarmentioning
confidence: 99%
“…ere are various competitive facility location models depending on the components to be considered. ese components usually include competitive type, location space, and customer behavior (see survey paper [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Ashtiani [29] indicated that some new features (such as relocation, design etc.) are included in the recent progress of competitive facility location problem.…”
Section: Introductionmentioning
confidence: 99%